Primera Conferencia de Centros de Estudios Cooperativos Bolivarianos - Restrepo R., Carlos; Bernal Restrepo, Gustavo; Agudelo Osorio, Bertulfo (Estudios de Derecho, 1944)
Primera Conferencia de Centros de Estudios Cooperativos Bolivarianos